Unveiling the Link Between Numeracy Skills and Self-Efficacy: A Study on Physics Learning Through AKM Assessments - Fathiah Alatas; Amrizaldi; Jannatun Latifah; Agus Budiyono; Andi Marwanti Panre (Program Studi Pendidikan Fisika, Universitas PGRI Semarang, 2025)
This study explores the relationship between numeracy skills and self-efficacy among grade 10 students within the context of the Minimum Competency Assessment (AKM) in physics, focusing on linear and parabolic motion. Employing a quantitative descriptive design, the research involved 140 students from a public high school in Bekasi, Indonesia. Instruments included a numeracy test comprising 17 AKM-based physics questions and a self-efficacy questionnaire adapted from Bandura's framework, covering the dimensions of level, generality, and strength. Results indicated that most students (53%) were at the